Pengaruh Pendidikan K3 Tentang APD Terhadap Pengetahuan Pekerja Karet PTPN XIV Teluk Elpaputih Kecamatan Teluk Elpaputih - Ira Sandi Tunny (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2021)
The majority of workers think that the work procedure with PPE has been quite long because there have been no serious complaints after carrying out this work. However, it was found that several workers had injuries to their hands due to being hit by knives, this occurred due to not using gloves as a form of PPE, and some of these workers even required special treatment and had to take time off work. This research aims to determine the knowledge of rubber workers before and after being given counseling about PPE as well as the influence of occupational safety and health education about PPE on rubber workers at PTPN XIV Teluk Elpaputih, Teluk Elpaputih District, Central Maluku Regency. This research uses a quasi-experimental method with a one-group pre-post test design approach. This research sample used a total sampling method, totaling 63 respondents. The research instrument uses a questionnaire. Data processing with SPSS uses the Wilcoxon nonparametric test. The Wilcoxon test results showed that 1 respondent's knowledge had decreased. 58 respondents' knowledge increased and 4 respondents' knowledge remained the same. From the research results it can be concluded that the knowledge of rubber workers before being given treatment reached the lowest score for respondents was 4 people and the knowledge of respondents after being given treatment that reached the highest score for respondents was 10 people. And there is the influence of occupational safety and health education regarding PPE (personal protective equipment).